The economic effects of financial derivatives on corporate tax avoidance - Donohoe, Michael P. (Journal of Accounting and Economics, 2015)
This study estimates the corporate tax savings from financial derivatives. I document a 3.6 and 4.4 percentage point reduction in three-year current and cash effective tax rates (ETRs), respectively, after a firm initiates a derivatives program. The decline in cash ETR equates to 10.69 million in tax savings for the average firm and 4.0 billion for the entire sample of 375 new derivatives users. Of these amounts, 8.75 million and 3.3 billion, respectively, are incremental to tax savings that theory suggests are a byproduct of risk management. Collectively, these findings provide economic insight into the prevalence of derivatives-based tax avoidance.